2010
DOI: 10.1007/s00467-010-1638-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cardiovascular effects of pre-transplant native kidney nephrectomy in children

Abstract: Left ventricular (LV) hypertrophy (H) and hypertension are prevalent in children with end-stage renal disease (ESRD) and after renal transplantation. Severe hypertension prior to renal transplantation has traditionally been an indication for native kidney nephrectomy. The impact of nephrectomy on cardiovascular disease has not been well documented. We retrospectively evaluated echocardiographic and ambulatory blood pressure monitoring (ABPM) data in 67 young adults who had undergone transplantation in the pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…For some underlying renal diseases there was variation in the management of unilateral PTNN both in our series and other reported series [5]. It is unclear whether unilateral PTNN is adequate, or if bilateral PTNN is performed whether this should be a synchronous or staged procedure.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For some underlying renal diseases there was variation in the management of unilateral PTNN both in our series and other reported series [5]. It is unclear whether unilateral PTNN is adequate, or if bilateral PTNN is performed whether this should be a synchronous or staged procedure.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies describing effects of PTNN on children with focal segmental glomerulosclerosis (FSGS) have suggested that bilateral nephrectomy prior to transplant reduces the risk of recurrent disease in the graft, but the controlled data to support this are lacking [4]. In a recent series examining cardiovascular effects of hypertensive children with established renal failure (ERF), almost half of the children had undergone PTNN, and no additional benefit was seen in those undergoing bilateral procedures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, native nephrectomies are performed prior to or at the time of transplant to help with management of hypertension (22). However, this is becoming an uncommon practice because recent data suggest that the benefit is limited (23). …”
Section: Etiology Of Hypertensionmentioning
confidence: 99%
“…Indications were drug-resistant proteinuria in six children, recurrent upper tract urosepsis in another six children, refractory hypertension in four children, malignancy/ malignant predisposition in four children and concomitant procedure during ureterocystoplasty in one child [8]. [6,[17][18][19][20][21][22][23][24]. Many causes of ESRD are associated with loss of proteins in urine.…”
Section: Indications For Native Nephrectomymentioning
confidence: 99%
“…Hypertension is common in patients with chronic kidney disease and may be caused by fluid overload or by increased renin secretion [20]. Cavallini, et al [21] compared retrospectively young adults who had undergone RTx in the pediatric age (with a mean follow-up of 10 years) with or without NN for hypertension. Fourteen patients had undergone a bilateral pre-RTx NN, 18 had undergone a unilateral NN, mostly at the time of transplantation and the native kidneys were left in place in the remaining 35 patients.…”
Section: Hypertensionmentioning
confidence: 99%